2014
DOI: 10.5588/ijtld.13.0468
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the MTBDRsl assay in Georgia

Abstract: Setting The country of Georgia has a high burden of multidrug and extensively drug-resistant tuberculosis (M/XDR-TB). Objective To assess the performance of the Genotype MTBDRsl assay in the detection of resistance to Kanamycin (KAN), Capreomycin (CAP), Ofloxacin (OFX), and XDR. Design Consecutive AFB smear positive sputum specimens identified as MDR by MTBDRplus testing were evaluated with the MTBDRsl assay and conventional second-line drug susceptibility testing (DST). Results Among 159 specimens, ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 21 publications
(23 reference statements)
1
38
0
Order By: Relevance
“…However, the sensitivity rate for OFL in our study was higher than those reported by Tukvadze et al [17] and Jin et al [18]. Our results were consistent with those of the meta-analysis study of Theron et al [19] in which performance of the GenoType MTBDRsl method was evaluated by analyzing 21 studies.…”
Section: Fluoroquinolones (Ofl Moxi)supporting
confidence: 63%
“…However, the sensitivity rate for OFL in our study was higher than those reported by Tukvadze et al [17] and Jin et al [18]. Our results were consistent with those of the meta-analysis study of Theron et al [19] in which performance of the GenoType MTBDRsl method was evaluated by analyzing 21 studies.…”
Section: Fluoroquinolones (Ofl Moxi)supporting
confidence: 63%
“…However, they should still have a sensitivity of ϳ90% for KAN r in countries, such as India and South Africa, where we observed KAN r being associated mostly with rrs mutations. The lack of eis probes in these LPAs likely contributed to the poor sensitivity (ϳ50%) recently reported for the MTBDRsl assay for the detection of aminoglycoside-resistant isolates from the country of Georgia (42). Adding eis promoter SNPs (Ϫ10G¡A, Ϫ12C¡T, and Ϫ14C¡T) to existing second-line LPAs and future molecular diagnostics would increase their utility globally and provide added confidence for the detection of KAN r in regions where rrs/eis frequencies are not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…All sputum samples had AFB cultures performed with the use of Löwenstein-Jensen solid media and standard methodologies as previously reported (24,25). Positive cultures were confirmed to be Mtb complex with the use of phenotypic tests and the Genotype MTBDRplus assay (Hain Lifescience; www.hain-lifescience.de) (24,25).…”
Section: Sputum Smear and Culture And Drug-susceptibility Testingmentioning
confidence: 99%
“…A smear microscopy was performed at the NCTLD by the National Tuberculosis Reference Laboratory with the use of Ziehl-Neelsen staining as previously described (24,25). All sputum samples had AFB cultures performed with the use of Löwenstein-Jensen solid media and standard methodologies as previously reported (24,25). Positive cultures were confirmed to be Mtb complex with the use of phenotypic tests and the Genotype MTBDRplus assay (Hain Lifescience; www.hain-lifescience.de) (24,25).…”
Section: Sputum Smear and Culture And Drug-susceptibility Testingmentioning
confidence: 99%
See 1 more Smart Citation